THE LOYALTY OF GARUDA INDONESIA CUSTOMERS TO THE ROUTE OF JAKARTA-SURABAYA - Aisyah Rahmawati (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2015)
Survey methods are used to determine the effect of pricing policy implementation (X1), quality of service (X2), and customer loyalty (Y) on PT. Garuda Indonesia, for Jakarta-Surabaya route in 2014. With a population of 773 154 passengers and a sample of 400 respondents, the data is obtained through questionnaires using Likert scale. With a simple and multiple linear regression analyses, simple and partial correlation, with significance level at α = 0.05, it was found that, first, there is a positive relationship between pricing policy and customer loyalty. The variation that occurs in customer loyalty is determined by pricing policy. Secondly, there is a positive relationship between service quality and customer loyalty. The variation that occurs in customer loyalty is determined by service quality. Third, there is a positive influence of pricing policy and service quality on customer loyalty with the coefficient of determination ry1.22 = 0.354, so 35.4% variation happening to customer loyalty is determined simultaneously by pricing policy and service quality. The implication proves that customer loyalty can be enhanced by improving the pricing policy and service quality.